Cerebriform sebaceous nevus: a subtype of organoid nevus due to specific postzygotic FGFR2 mutations. (22nd May 2021) - Theiler, M.; Weibel, L.; Christen‐Zaech, S.; Carmignac, V.; Sorlin, A.; Neuhaus, K.; Chevarin, M.; Thauvin‐Robinet, C.; Philippe, C.; Faivre, L.; Vabres, P.; Kuentz, P.
Abstract: Background: Postzygotic mutations in FGFR2 have been identified in mosaic forms of acne, keratinocytic epidermal nevi, nevoid acanthosis nigricans / rounded and velvety epidermal nevus and in two fetuses with papillomatous pedunculated sebaceous nevus (PPSN). Objectives: To determine the clinical and genetic characteristics of children with cerebriform, papillomatous and pedunculated variants of sebaceous nevi. Methods: Infants diagnosed with sebaceous nevi characterized by a cerebriform, papillomatous and/or pedunculated morphology over a 10‐year period (2010–2019) at three paediatric dermatology centres in Switzerland and France were included in this case series. Clinical and histological characteristics were assessed. Next‐generation sequencing was used to assess for FGFR2 mutations. Results: All nevi were located on the head, with a rounded or linear shape and a typical cerebriform, sometimes papillomatous and pedunculated, surface. No associated extracutaneous anomalies were found. Nevi harboured postzygotic mutations in the transmembrane domain of FGFR2 in 6/8 children (75%), either the known specific p.(Cys382Arg) mutation in 5 cases, or a novel mutation, p.(Val395Asp), in one. Conclusions: We found an exquisite genotype–phenotype correlation in these rare nevi, with specific postzygotic mutations in the transmembrane domain of FGFR2 . As not all lesions were truly papillomatous and pedunculated, the term cerebriform sebaceous nevus (CSN) appears more suitable than PPSN to describe this entity. The cerebriform pattern of CSN is reminiscent of cutis gyrata, as seen in Beare–Stevenson syndrome, which is caused by closely related germline FGFR2 mutations. While clinically impressive, CSN seem to carry a good prognosis and a low risk for extracutaneous associations.